Aplication IoT for Monitoring and Automatic Control of Water Levels Using Virtuino - Salahuddin, Salahuddin; Bakhtiar, Bakhtiar; Akbar, Muhammad Ramzil; Munazzar, Sayed; Nasir, Muhammad (Politeknik Negeri Lhokseumawe, 2025)
Control and monitoring of water tanks in the Information and Computer Technology (ICT) Building of the Lhokseumawe State Polytechnic still experience limitations regarding filling and supervision in the tank. Water will continue to fill the tank and indirectly will result in energy waste and can also cause damage to the pump if the water in the main well has run out. The automatic monitoring and control system for filling water tanks for the Information and Computer Technology building uses ATmega 328 as a microcontroller that will control the entire system, Ultrasonic Sensors to measure water levels, relays as pump automation, flow meter sensors as detectors of water flow to the tank and the esp8266 module is used to send data to android using the virtuino application. Monitoring the water level when filling this tank is expected to be one step in saving water and energy. Based on testing, the average delay response of the virtuino display using WiFi and simcard. The delay on and off the pump will be calculated. This condition can be overcome by implementing the internet of things (IoT) on the tank in the Information and Computer Technology Building. The system to be built uses the Virtuino display.